(untitled) (African Journal of Biomedical Research, 2023)
Healthcare workers play a vital role in society by providing essential medical care and services. However, their occupational environment exposes them to a diverse range of hazards that can influence their health and well-being. This review aims to provide a comprehensive overview of the occupational hazards faced by healthcare workers and the associated risks, focusing on healthcare settings such as hospitals, clinics, and laboratories. The study synthesizes existing literature on various types of hazards that healthcare workers encounter. These hazards include biological risks, such as exposure to infectious agents like viruses, bacteria, and fungi; chemical exposures from hazardous drugs, disinfectants, and sterilizing agents; physical hazards like ergonomic strain, needle stick injuries, and radiation exposure; and psychosocial hazards including stress, burnout, and workplace violence. In addition to identifying the factors that predispose the workers to these hazards, implementation of proper measures, use of personal protective equipment, ergonomic improvements, comprehensive training programs, and mental health support initiatives are discussed as vital steps in preventing the well-being of healthcare workers. The findings in this review emphasize the need for comprehensive interventions, including improved training programs, implementation of safety protocols, the provision of adequate personal protective equipment, and enhanced support systems. As the healthcare landscape continues to evolve in Nigeria, understanding and addressing occupational hazards is vital for ensuring the health and safety of healthcare workers, which can be achieved by raising awareness about the multifaceted challenges faced by healthcare professionals.